Respuesta :
Answer:
Using Green's theorem we have:
int F.dr = int int d/dx ((y^2-x^2)/(x^2+y^2)^2) - d/dy (2xy/(x^2+y^2)^2) =
(2x^3 - 6xy^2) / (x^2+y^2)^3 - (2x^3 - 6xy^2) / (x^2+y^2)^3 = 0
Therefore:
int F.dr = 0
Step-by-step explanation:
Answer:
Around a close curve [tex]\oint_c \vec F \cdot dr=0[/tex] .
Step-by-step explanation:
Given information:
[tex]F(x, y) = \frac{2xyi + (y^2-x^2)j }{(x^2 + y^2)^2}[/tex]
If function is in form of,
[tex]\vec F=Pi+Qj[/tex] and C is any positively oriented simple closed curve that encloses the origin.
Then,by use of Green's theorem
[tex]\int\int_{R}(\frac{\partial Q}{\partial x}-\frac{\partial P}{\partial y})dA= \oint_c \vec F \cdot dr[/tex]
By partial differentiation
[tex]\frac{\partial Q}{\partial x}=[/tex][tex]\frac{2x^3-6xy^2}{(x^2+y^2)^3}[/tex]
[tex]\frac{\partial P }{\partial y}=\frac{2x^3-6xy^2}{(x^2+y^2)^3}[/tex]
On substitution in Green's theorem,
We get,
[tex]\int\int_{R}(\frac{2x^3-6xy^2}{(x^2+y^2)^3}-\frac{2x^3-6xy^2}{(x^2+y^2)^3})dA= \oint_c \vec F \cdot dr[/tex]
[tex]\oint_c \vec F \cdot dr=0[/tex]
Hence, around a close curve [tex]\oint_c \vec F \cdot dr=0[/tex] .
For more details please refer link:
https://brainly.com/question/2758275?referrer=searchResults